Brackish Water Treatment into raw water using Moringa oleifera leaves as an adsorber at Habibie Mustafa College, Keramat Kubah Village, Tanjungbalai Town - Ardilla, Desi; Rangkuti, Khairunnisa; Taufik, Muhammad (Talenta Publisher, 2020)
This work aims to provide raw water from brackish water by reducing the salt content in brackish water to fresh water using the column method. Moringa leaves were chosen as the adsorber considering their high availability in partner locations. The location chosen was Habibie Mustafa's college in Tanjungbalai, North Sumatra. Brackish water treatment equipment is designed using a distillation system. In the column refining, the filter tubes used are made using PVC pipe with a height of 45 cm (Moringa leaves), a height of 35 cm (sand), and a height of 25 cm (charcoal). Each filter media in the tube is limited by using a palm fiber. The use of fibers is used as a barrier between the filter media so that the filter media remains in its position during the filtration process so that there is no mixing of the filter media in the filter tube. The results obtained are clean water that can be consumed according to drinking water quality standards. The results obtained were raw water with TDS specifications = 405 mg / L, turbidity 4 NTU, sulfate = 240 mg / L zinc = 2 mg / L, and Mn = 0.35 mg / L. The results obtained are still on the threshold of drinking water quality standard requirements by the Minister of Health of the Republic of Indonesia Number: 492 / Menkes / Per / IV / 2010 concerning drinking water quality requirements